Dosis de gallinaza y su efecto en las características agronómicas y rendimiento forrajero en dos tiempos de corte del pasto Panicum máximum cv. Mombaza en Zungarococha, Loreto – 2018 - Lopez Cumari, Carlos Renzo (2021)
The present investigation was carried out at the National University of the Peruvian Amazon at the Faculty of Agronomy in the Beef Project in the Fundo de Zungarococha, entitled Dose of Chicken and its effect on the agronomic characteristics and Forage Yield in two cut times of the Panicum Pasture. maximum cv. Mombaza in Zungarococha, Loreto - 2018. Evaluations were carried out at the sixth and eighth week after sowing with vegetative seed (mattes), in plots of 5 m x 1.2 m (6 m2) and an experimental area of 450 m2. With a Complete Random Block Design (DBCA) design, with four treatments and four repetitions, the treatments under study were: T0 (0 tons of manure / ha / cut), T1 (10 tons of manure / ha / cut) , T2 (20 tons of manure / ha / cut) and T3 (30 tons of manure / ha / cut), obtaining the following results: For forage yield, the best result was obtained by applying treatment T3 (30 tons of manure) / ha / cut), in green matter and dry matter. That, at a higher dose of chicken manure, the yields of green, dry matter and plant cover of the grass Panicum maximun cv. Mombaza. That forage (Panicum maximun) cv Mombaza as time passes the production of green and dry matter increases.